The Application of Ing Ngarsa Sung Taladha, Ing Madya Mangun Karsa, Tut Wuri Handayani for Indonesian Language Education Students as an Effort to Improve Understanding of the Teaching Profession - Anisa Asari Dewi; Audrey Sabrina; Alya; Rani Hartati Simanjuntak; Viva El Kahfi; Nadra Amalia (Universitas Swadaya Gunung Jati, 2025)
This study aims to determine the meaning of KI Hajar Dewantara's three educational mottos, to understand how students as prospective teachers implement these mottos, and to measure teacher professionalism through these mottos. This study uses a qualitative descriptive method with interviews as the data collection technique. The subjects in this study are Indonesian Language and Literature Education students as prospective teachers, selected through simple random sampling. The results of this study answer the researcher's curiosity, namely that these educational mottos are more than just slogans; they serve as concrete guidelines in building teacher professionalism, particularly in terms of personality. A teacher who can serve as a role model, motivator, and supporter for students will create a learning environment that is not only knowledge-oriented but also focused on character development. Therefore, it is important for prospective educators to familiarize themselves with these principles from an early stage, so that they can later deliver humanistic, inspiring education and produce a generation that is intelligent, competitive, and of noble character.